A minimal viable process and tools for massive participation in urban development. (21st April 2020) - Stelzle, Benjamin; Naumann, Fabrice; Holmer, Torsten; Jannack, Anja; Noennig, Jörg Rainer
The paper aims at providing a framework for enabling massive citizen participation in urban planning projects. Derived from a structured analysis of existing formal and informal citizen participation processes in urban development we developed a comprehensive process supported by a set of digital tools for massive participation. This so-called minimal viable process fulfils: a) good practice standards for participation while b) utilising as few as possible technical means and procedural steps. The newly developed procedure ensures proper citizen involvement from the very start of a project up to design selection. The framework involves all necessary stakeholder groups, who are addressed by specific tools and algorithms. The results of a test run indicate the general applicability of the process and the tools, and provided insight for the further technical development of the IT tools and the procedure itself within the H2020 project "U_CODE Urban Collective Design Environment".